Frequency Dependence of the Internal Friction of the AMg6 Alloy; Journal of Machinery Manufacture and Reliability; Vol. 50, iss. 3 - Tomilin A. K. Aleksander Konstantinovich; Kuznetsov F. Yu. Fedor Yurjevich; Konovalenko I. S. Ivan Sergeevich; Druzhinin N. V. Nikolay Vladimirovich; Krasnoveykin V. A. Vladimir Alekseevich; Smolin I. Yu. Igor Yurievich (2021, 2021)
Title screen